Inspiratory muscle endurance in patients with chronic heart failure. Issue 4 (October 1996) - Walsh, J. T.; Andrews, R.; Johnson, P.; Phillips, L.; Cowley, A. J.; Kinnear, W. J.
Abstract : OBJECTIVE: To assess the significance of changes in respiratory muscle endurance in relation to respiratory and limb muscle strength in patients with mild to moderate chronic heart failure using a threshold loading technique. SUBJECTS: 20 patients with chronic heart failure (17 male) aged 63.8 (SD 7.4) years and 10 healthy men aged 63.1 (5.6) years. Heart failure severity was New York Heart Association (NYHA) grade II (n = 11) and NYHA grade III/IV (n = 9). METHODS: Respiratory muscle strength was measured from mouth pressures during maximum inspiratory effort (MIP) at functional residual capacity (FRC) and limb muscle strength was measured using a hand grip dynamometer. Inspiratory muscle endurance was measured using a threshold loading technique. The total endurance duration, the maximum threshold pressure achieved (P-Max), and the inspiratory load (% ratio of P-Max/MIP) were recorded in all subjects. RESULTS: Inspiratory muscles were weaker in patients with heart failure than in the controls [MIP 53.6 (16.5) v 70.9 (20.2) cm H2O, P < 0.05]. Hand grip strength was similar in both subject groups [31.6 (SD) v 36.1 (15.9) dynes]. Total endurance duration was significantly reduced in the patient group [494 (223) v 996 (267) s, P < 0.01], as was the maximal threshold pressure achieved [P-Max 18.5 (6.4) v 30.7 (6.6) cm H2O, P < 0.01]. When expressed as a percentage of MIP, P-Max was also lower in the patients [35.2 (11.8) v 44.8 (11.4)%, P < 0.05]. There was no significant correlation between any measure of endurance and limb muscle strength. CONCLUSIONS: Respiratory muscle endurance is reduced in patients with chronic heart failure. These changes probably reflect a generalised skeletal myopathy and provide further evidence of respiratory muscle dysfunction in patients with this disease. Respiratory muscle endurance needs now to be related to symptoms and the effects of treatment and respiratory muscle training should also be explored.